2023
DOI: 10.3324/haematol.2022.282289
|View full text |Cite
|
Sign up to set email alerts
|

The Geriatric Prognostic Index: a clinical prediction model for survival of older diffuse large B-cell lymphoma patients treated with standard immunochemotherapy

Abstract: International prognostic Index (IPI) is the most widely used clinical prediction model for diffuse large B-cell lymphoma (DLBCL) patients treated with rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone (R-CHOP), but may be suboptimal in older patients. We aimed to develop and externally validate a clinical prediction model for older, R-CHOP treated DLBCL patients by examining geriatric assessment and lymphoma-related parameters in real-world cohorts. A population-based training set of 365 R-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“… 14 , 15 When assessing the objective health of older adults across multiple domains, including cognitive impairment, functional or physical impairment, and multimorbidity, geriatric assessment may affect cancer prognosis, treatment choices, and tolerance. 16 , 17 , 18 , 19 , 20 , 21 Notably, the G‐8 screening tool has demonstrated high sensitivity and acceptable specificity, and possess prognostic value in hematological malignancies. 22 , 23 The Vulnerable Elders Survey‐13 is a stronger predictor of 1‐year mortality in older patients with DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 When assessing the objective health of older adults across multiple domains, including cognitive impairment, functional or physical impairment, and multimorbidity, geriatric assessment may affect cancer prognosis, treatment choices, and tolerance. 16 , 17 , 18 , 19 , 20 , 21 Notably, the G‐8 screening tool has demonstrated high sensitivity and acceptable specificity, and possess prognostic value in hematological malignancies. 22 , 23 The Vulnerable Elders Survey‐13 is a stronger predictor of 1‐year mortality in older patients with DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that low NKCC4 synergistically decreased the OS and PFS among DLBCL patients with high IPI. IPI is now still the most extensive utilized prognostic index in DLBCL, although in the era of rituximab, which notably improves patient cure ratio [ 26 , 27 ]. However, the use of IPI, revised-IPI, or National Comprehensive Cancer Network IPI to classify high-risk subgroup with long-term survival less than 50% is limited [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated that the new index performed better than conventional prognostic indices like the International Prognostic Index (IPI), the Revised (R)-IPI, and the National Comprehensive Cancer Network (NCCN)-IPI. 1 …”
mentioning
confidence: 99%